2000
DOI: 10.1007/pl00006834
|View full text |Cite
|
Sign up to set email alerts
|

Living ring-opening polymerization of ɛ-caprolactone with combinations of tert-butyllithium and bilky aluminium phenoxides

Abstract: The polymerization of -caprolactone (-CL) with a combination of tert-butyllithium (t-BuLi) and bis(2,6-di-t-butylphenoxy)methylaluminum [MeAl(ODBP) 2 ] in toluene at 0°C proceeded in a living manner to give polymers with narrow molecular weight distributions (MWD) within a few minutes, while the polymerization with t-BuLi alone gave a polymer with much broader MWD. The yield of the polymer did not reach 100 % at the Al/Li ratio of 5, because the excess MeAl(ODBP) 2 coordinates with -CL to protect it from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The proposed Scheme 9 ROP of e-CL catalysed by LDA. 34 Scheme 10 ROP of e-CL catalysed by cyclopentadienyl sodium. 36 Scheme 11 ROP of e-CL using bis(tetrahydrofuran)calcium bis[bis(trimethylsilyl)amide]-alcohol system, adapted from Zhong et al 43 mechanism for the following steps is shown in Scheme 12.…”
Section: Alkali-based Catalysts Alkali Metal-based Catalysts (Esiw Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The proposed Scheme 9 ROP of e-CL catalysed by LDA. 34 Scheme 10 ROP of e-CL catalysed by cyclopentadienyl sodium. 36 Scheme 11 ROP of e-CL using bis(tetrahydrofuran)calcium bis[bis(trimethylsilyl)amide]-alcohol system, adapted from Zhong et al 43 mechanism for the following steps is shown in Scheme 12.…”
Section: Alkali-based Catalysts Alkali Metal-based Catalysts (Esiw Tablementioning
confidence: 99%
“…At low catalyst concentration, not only one, but both of the Al-alkyl bonds participated in the polymerisation process. Different Al complexes based on salicylaldimines (ESIw Table 1.3, entries [32][33][34][35] with different substituents on the imino group, showed an increasing activity in the substituent order C 6 F 5 -44 2,6-i PrC 6 H 3 -44 tert-butyl-4 adamantyl-. 68 The effect of different substituents on the two phenyl rings of the ligand (e.g.…”
Section: Alkali-based Catalysts Alkali Metal-based Catalysts (Esiw Tablementioning
confidence: 99%
“…[5][6][7][8] However, the study of polyesters generated from ring-opening polymerization using non-tin metal alkoxides as catalysts has just started to attract researchers' attention. Among those metal alkoxides, aluminum, [9][10][11][12][13][14][15] lithium, [16,17] titanium, [18][19][20][21] and some lanthanide metals [22][23][24][25][26][27] have been studied by different groups. We have previously examined the ring-opening polymerization of ε-caprolactone and lactide with aluminum alkoxides supported by monoanionic bidentate ketiminate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Besides manipulating the active species responsible for propagation and fine-tuning their reactivity, another approach has been to selectively activate the monomers as a means to favor propagation over scrambling reactions. Using bis­(2,6-di- tert -butyl­phenoxy)­ethylaluminum to activate ε-caprolactone, Kitayama et al could, for instance, successfully anionically polymerize ε-caprolactone under controlled/living conditions . Recently, Waymouth and co-workers demonstrated the ability of dithioureas to selectively activate the carbonyl function of both lactones and lactides, also observed that propagation is vastly favored over transesterification, and succeeded in their attempt to obtain a truly living polymerization of cyclic esters. , In this article, we describe a totally novel strategy based on the use of CO 2 along with simple lithium alkoxides as a means to bring about the controlled/living anionic ring-opening polymerization of cyclic esters.…”
Section: Introductionmentioning
confidence: 99%